Gender, self-image and leadership: a gender-specific comparison of the self-images of female and male leaders - Brigitte Streibich; Christoph Desjardins (Journal of Applied Leadership and Management, 2019)
Research questions: Are men and women in leadership roles different? How do the self-images of male and female leaders differ? Is there a linkage between leadership, gender and self-image? Methods: Based on a comprehensive overview of relevant theoretical concepts and scientific literature, the Leadership Tasks Survey was used for a selfassessment of 91 German leaders. The collected data was processed and statistically analyzed. Results: The concepts of leadership, gender and self-image are strongly linked to each other. Differences exist between the self-images of men and women in leadership positions with women having the more negative, self-critical selfimage. These differences were found to be statistically significant.
Keywords: 650